I diuretici dell’ansa nella terapia di mantenimento del paziente con scompenso cardiaco - Cecchi, Franco (Farmeconomia. Health Economics and Therapeutic Pathways, 2004)
Diuretics are still a cornerstone of acute heart failure. Their role in chronic heart failure has recently been reconsidered, as Ace-inhibitors and Beta-blockers have been shown to be highly effective in reducing cardiovascular morbidity and mortality in patients with heart failure. Loop diuretics and aldosterone antagonists, however, are still used in chronic heart failure, at the lowest dose needed in order to mantain haemodynamic balance. The use of effective loop diuretics with longer half-lives and constant bioavailability may be beneficial, resulting in fewer hospital readmissions, both for congestive heart failure and all cardiovascular events, in improved quality of life and in health costs reduction.